2022
DOI: 10.1177/15459683221143464
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Trajectories of Post-Stroke Depression Symptom Subgroups

Abstract: Background Post-stroke depressive symptoms are prevalent and impairing, and elucidating their course and risk factors is critical for reducing their public health burden. Previous studies have examined the course of post-stroke depression, but distinct depressive symptom dimensions (eg, somatic symptoms, negative affect [eg, sadness], anhedonia [eg, loss of interest]) may vary differently over time. Objective The present study examined within-person and between-person associations between depressive symptom di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Only the chronic group showed a decreased sense of vigor-activity related to anhedonia, suggesting the long-term negative impact of anhedonia on engaging in a healthy active lifestyle. These results are in line with a recent previous study suggesting the role of anhedonia as a predictor of somatic symptoms of depression, such as fatigue, over the first year after discharge from rehabilitation (Ashaie et al, 2023). Our findings also underlines the likely role of anhedonia in generating a deteriorating looping effect at a behavioral level (Mallorqui et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Only the chronic group showed a decreased sense of vigor-activity related to anhedonia, suggesting the long-term negative impact of anhedonia on engaging in a healthy active lifestyle. These results are in line with a recent previous study suggesting the role of anhedonia as a predictor of somatic symptoms of depression, such as fatigue, over the first year after discharge from rehabilitation (Ashaie et al, 2023). Our findings also underlines the likely role of anhedonia in generating a deteriorating looping effect at a behavioral level (Mallorqui et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…Despite the substantial overlap between apathy and anhedonia, the former is associated with an impairment in selecting future behaviors based on emotional signals, while anhedonia is characterized by diminishing sensitivity to everyday pleasures and positive mood, crucial aspects for goal-directed engagement in rewarding activities ( Verrienti et al, 2023 ). Considering the role of anhedonia in motivational aspects crucial for stroke survivors’ recovery, a recent study by Ashaie et al (2023) explored the association between three dimensions of PSD somatic symptoms, negative affect, and anhedonia. They found that anhedonia predicted subsequent increases in somatic symptoms during the first year after rehabilitation discharge, indicating its impact on physical distress rather than stroke itself.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation